It’s All At the Mall: Exploring Present Shopping Experiences - Lather, Anu Singh; Kaur, Tripat (Indian Journal of Marketing, 2006)
The research examined the influence of selected attributes on store patronage for doing shopping. When the market is flooded with products-branded and unbranded. The shoppers are in a dilemma to buy which one! The shoppers are really jostled with variety of brands and their mind is boggling where to stop for shopping? Shopper basically decides on the basis of store characteristics. The quality of stores taken together form the overall image of mall. They are basically exploring the shopping experiences in the malls. These changes in consumer behavior also augur well for the retailing industry. The organized retail chains, display all the products and the most attractive product catches the customer attention of shoppers. Most of these stores believe in creating not just a marketing activity with its customers, but rather favour relationship building with him so as to convert first time customers into a client. The Study concentrates on organized retailing, which consists of shopping malls coming up a big way in India. The decision to patronize a particular store usually starts with a set of characteristics or attributes that shoppers consider important. Retailers then use these attributes to make decisions regarding what store or stores can cater to their particular needs to different age cohorts with different promotional tools. Past retail and marketing studies have identified several shoppers-oriented store attributes such as price, quality, variety and discounts but these studies overlooked how the physical environment, store reputation and store location affects retail store patronage. In response to different demographic features of shoppers, entrepreneurs have developed new way to provide merchandising and rendering services so that a new fervour could be smelt and as a sequel totally new ambience could be experienced. Keeping these facts, the researchers have studied the nine characteristics of malls to elaborate the enthralling shopping experiences. This will provide academics, mall developers and retailers a richer understanding of various components that contribute to malls experiences, and allow them to more effectively study and market to this segment.